Development of Mobile Learning integrated with Learning Management System (LMS) on Buffer Solutions Topic - Ucu Cahyana; Farihatul Janah; Setia Budi (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This research aims to develop mobile learning integrated with LMS and test its effectiveness motivation learning on the topic of buffer solutions. The research was conducted at SMA AL-HASRA from November 2020 to June 2021. The research and development method by Borg and Gall was used by modifying five stages, needs analysis; product development; validation; product testing; and implementation. Testing used quantitative method with post-test only control group design and analysis using independent sample t-test. The resulting mobile learning medium is called